Value chain analysis of the Kenyan poultry industry: The case of Kiambu, Kilifi, Vihiga, and Nakuru Districts - Okello, Julius J.; Gitonga, Zachary; Mutune, Jane; Okello, Ruth M.; Afande, Martin; Rich, Karl M. (International Food Policy Research Institute, 2010)
The Kenyan poultry industry is characterized by dualism, comprised of both smallholder and large-scale poultry producers. The industry is characterized by two main production systems namely (i) the commercial hybrid poultry production system and (ii) the indigenous poultry production system. This study examines the poultry industry in Kenya with the aim of identifying the actors, assessing poultry and poultry product flows, and highlighting some of the policies and regulations relevant to potential outbreaks of highly pathogenic avian influenza (HPAI) in Kenya. Specific aims included: